2022
DOI: 10.3389/fmicb.2022.1088179
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary supplementation probiotic complex on growth performance, blood parameters, fecal harmful gas, and fecal microbiota in AA+ male broilers

Abstract: In this study, Bacillus subtilis, Clostridium butyricum and Enterococcus faecalis were made into a probiotic complex (PC). The PC was supplemented in AA+ male broilers’ diets to investigate the effects of PC on broiler growth performance, carcass traits, blood indicators, harmful gas emissions in feces and microbiota. Three hundred and sixty 1-day-old AA+ male broilers with an average initial body weight (data) were randomly divided into 3 dietary treatments of 6 replicates each, with 20 birds per replicate. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Our results showed that administration of L. fermentum 2i3 at a dose of 1 × 10 9 CFU/mL of drinking water had a positive effect on some production parameters such as feed conversion ratio and weekly weight gain. Likewise, several recent studies have reported that commercial probiotic products in which the concentration of probiotic bacteria used is at least 1 × 10 8 CFU/g of feed, demonstrably improve production parameters as well as the immune response of broiler chickens ( Rehman et al, 2020 ; Fesseha et al, 2021 ; Zou et al, 2022 ). Most authors believe that the beneficial effects of probiotics can be increased by selecting “strong strains”, combining 2 or more strains, gene manipulation, or even the increasingly popular combination of probiotics and other synergistic substances of natural origin.…”
Section: Discussionmentioning
confidence: 96%
“…Our results showed that administration of L. fermentum 2i3 at a dose of 1 × 10 9 CFU/mL of drinking water had a positive effect on some production parameters such as feed conversion ratio and weekly weight gain. Likewise, several recent studies have reported that commercial probiotic products in which the concentration of probiotic bacteria used is at least 1 × 10 8 CFU/g of feed, demonstrably improve production parameters as well as the immune response of broiler chickens ( Rehman et al, 2020 ; Fesseha et al, 2021 ; Zou et al, 2022 ). Most authors believe that the beneficial effects of probiotics can be increased by selecting “strong strains”, combining 2 or more strains, gene manipulation, or even the increasingly popular combination of probiotics and other synergistic substances of natural origin.…”
Section: Discussionmentioning
confidence: 96%
“…In this experiment, drinking water containing NaDCC significantly reduced NH 3 and H 2 S emissions from feces. Previous reports have shown that when the number of E. coli and Salmonella in feces is reduced, fecal NH 3 and H 2 S emissions are also reduced ( 43 ). Prolonged exposure of broilers to NH 3 has been shown to affect the structure of their cecal flora and, consequently, their growth performance ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic are mono or mixed cultures of live microorganisms which can be administrated via different routes to broiler chickens, confer an improvement in intestinal microbiota, structure and mucosal immunity (Li et al, 2020;Wang et al, 2021). Moreover, a lot of previous studies illustrated the affirmative effects of probiotics in ameliorating digestibility and absorption of nutrients (Zhang et al, 2022), insulating harmful microorganisms (Gao et al, 2019;Biswas et al, 2022), enhancing growth performance (Arteaga et al, 2020;Zou et al, 2022), improving carcass characteristics and raising health parameters of broilers (Li et al, 2020;Khochamit et al, 2020). As mentioned, attention has been shifted to natural growth promoters as alternatives to antibiotics, which include organic acids (Elnesr et al, 2021).…”
Section: Recentmentioning
confidence: 99%